Dynamics of Fuzzy BAM Neural Networks with Distributed Delays and Diffusion - Qianhong Zhang; Lihui Yang; Jingzhong Liu (Journal of Applied Mathematics)
Constructing a new Lyapunov functional and employing inequality technique, the existence, uniqueness, and global exponential stability of the periodic oscillatory solution are investigated for a class of fuzzy bidirectional associative memory (BAM) neural networks with distributed delays and diffusion. We obtained some sufficient conditions ensuring the existence, uniqueness, and global exponential stability of the periodic solution. The results remove the usual assumption that the activation functions are differentiable. An example is provided to show the effectiveness of our results.